Anorexia nervosa and body dysmorphic disorder are associated with abnormalities in processing visual information. Issue 10 (July 2015) - Li, W.; Lai, T. M.; Bohon, C.; Loo, S. K.; McCurdy, D.; Strober, M.; Bookheimer, S.; Feusner, J.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Anorexia nervosa (AN) and body dysmorphic disorder (BDD) are characterized by distorted body image and are frequently co-morbid with each other, although their relationship remains little studied. While there is evidence of abnormalities in visual and visuospatial processing in both disorders, no study has directly compared the two. We used two complementary modalities – event-related potentials (ERPs) and functional magnetic resonance imaging (fMRI) – to test for abnormal activity associated with early visual signaling. Method We acquired fMRI and ERP data in separate sessions from 15 unmedicated individuals in each of three groups (weight-restored AN, BDD, and healthy controls) while they viewed images of faces and houses of different spatial frequencies. We used joint independent component analyses to compare activity in visual systems. Results AN and BDD groups demonstrated similar hypoactivity in early secondary visual processing regions and the dorsal visual stream when viewing low spatial frequency faces, linked to the N170 component, as well as in early secondary visual processing regions when viewing low spatial frequency houses, linked to the P100 component. Additionally, the BDD group exhibited hyperactivity in fusiform cortex when viewing high spatial frequency houses, linked to the N170 component. Greater activity in this component was associated with lower attractiveness ratings of faces. Conclusions Results provide preliminary evidence of similar abnormal spatiotemporal activation in AN and BDD for configural/holistic information for appearance- and non-appearance-related stimuli. This suggests a common phenotype of abnormal early visual system functioning, which may contribute to perceptual distortions.